Drug-induced Sarcoid Uveitis with Biologics. (19th May 2022) - Sobolewska, Bianka; Baglivo, Edoardo; Edwards, Albert O.; Kramer, Michal; Miserocchi, Elisabetta; Palestine, Alan G.; Schwab, Ivan R.; Zamir, Ehud; Doycheva, Deshka; Zierhut, Manfred
ABSTRACT: Purpose/Objectives: to evaluate new onset uveitis or reactivated uveitis by biologic agents and characterize their features. Materials and Methods: This is a multicenter, retrospective case series. Patients under biologic therapy were included if they developed uveitis for the first time or experienced intraocular inflammation which was different in location or laterality to previous inflammation. Results: Sixteen patients were identified. The underlying disorders included ankylosing spondylitis, juvenile idiopathic arthritis, rheumatoid arthritis, and Behçet's Disease. The biologic agents associated with a first episode of uveitis (n = 11) or with a new recurrence of uveitis (n = 5) were etanercept, adalimumab, abatacept, infliximab, and golimumab. Sarcoidosis based on bihilar lymphadenopathy, other computer tomography-findings, or biopsy was diagnosed in five patients under therapy with etanercep, adalimumab, and abatacept. Additionally, seven patients developed clinical changes in their uveitis pattern, suggesting sarcoid uveitis. Conclusions: Biologic treatment-induced uveitis often presents as granulomatous disease.